CRRTnet: a prospective, multi-national, observational study of continuous renal replacement therapy practices - Michael Heung; Sean M. Bagshaw; Andrew A. House; Luis A. Juncos; Robin Piazza; Stuart L. Goldstein (BMC Nephrology, 2017)
Abstract Background Continuous renal replacement therapy (CRRT) is the recommended modality of dialysis for critically ill patients with hemodynamic instability. Yet there remains significant variability in how CRRT is prescribed and delivered, and limited evidence-basis to guide practice. Methods This is a prospective, multi-center observational study of patients undergoing CRRT. Initial enrollment phase will occur at 4 academic medical centers in North America over 5 years, with a target enrollment of 2000 patients. All adult patients (18–89 years of age) receiving CRRT will be eligible for inclusion; patients who undergo CRRT for less than 24 h will be excluded from analysis. Data collection will include patient characteristics at baseline and at time of CRRT initiation; details of CRRT prescription and delivery, including machine-generated treatment data; and patient outcomes. Discussion The goal of this study is to establish a large comprehensive registry of critically ill adults receiving CRRT. Specific aims include describing variations in CRRT prescription and delivery across quality domains; validating quality measures for CRRT care by correlating processes and outcomes; and establishing a large registry for use in quality improvement and benchmarking efforts. For initial analyses, some particular areas of interest are anticoagulation protocols; approach to fluid overload; CRRT-related workload; and patient safety. Trial registration Registered on ClinicalTrials.gov 1/10/2014: NCT02034448.